Update the Past. New Animism as a Native “Rescue Perspective” - Filipowicz, Anna (Sensus Historiae, 2020)
For a post-dependence-oriented humanities, it is important not only to look into the future, but also towards the past, to the alternative to the Western tradition of thinking about the world. These include, for example, a new animism that doesn’t know the absolute divisions of man and animal, assuming the complementarity of human and non-human perspectives. Reaching for indigenous knowledge allows us to look for an exit from the Anthropocene impasse (scientific, social, political) and provides tools for changing reality. They are usually easily accessible and ready for immediate use.